Role of epigenetics in cellular reprogramming; from iPSCs to disease modeling and cell therapy. Issue 2 (19th October 2021) - Li, Yong; Darabi, Radbod
Abstract: Epigenetics play a fundamental role in induced pluripotent stem cell (iPSC) technology due to their effect on iPSC's reprogramming efficiency and their subsequent role in iPSC differentiation toward a specific lineage. Epigenetics can skew the differentiation course of iPSCs toward a specific lineage based on the epigenetic memory of the source cells, or even lead to acquisition of new cell phenotypes, due to its aberrations during reprogramming. This viewpoint discusses key features of the epigenetic process during iPSC reprogramming/differentiation and outlines important epigenetic factors that need to be considered for successful generation and differentiation of iPSCs for downstream applications.